PERLUASAN SKOP UNDANG-UNDANG ISLAM DI MALAYSIA: APLIKASI DAN IMPLIKASINYA: Extending The Scope of Islamic Law in Malaysia: Applications and Its Implications - Azhar, Alias; Hussain, Mohammad Azam (Jurnal Syariah, 2012)
Since the Parliament of Malaysia passed the Islamic Banking Act 1983 (Act 276), it has been shown that the scope of Islamic law implemented in Malaysia is no longer limited to the scope specified in List II of the Ninth Schedule of the Federal Constitution. Pursuant to List II, the scope of Islamic law is limited to personal law and religious offences only. The Islamic Banking Act 1983 (Act 276) in governing the Islamic banking and finance system has widened the scope of Islamic law. The implementation of an Islamic banking and financial system also has implications for the administrative aspects of Islamic law. The scope of Islamic law, as specified in List II, remains under the State’s jurisdiction. Meanwhile, the Federal’s jurisdiction has the power in governing and regulating Islamic banking and financial matters. This phenomenon also shows the impact of the judicial jurisdiction of the Syariah court and civil court over the scope of Islamic law in Malaysia. In this regard, the Syariah court retains its jurisdiction over the scope of Islamic law enunciated under List II. However, matters pertaining to Islamic banking and finance are subject to the jurisdiction of civil courts. Henceforth, this article seeks to analyze the implications that arise in respect of the administration of Islamic law under the Federal and State Legislature.